Pengaruh Board Diversity dan Intellectual Capital pada Nilai Perusahaan - Kristina, I Gusti Agung Rai; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
This researchis purposed to prove empirically the effect of board diversity and intellectual capital to firm value. The research using purposive sampling method where from 153 manufacturing companies listed in Indonesia Stock Exchange become the population obtained 56 companies for 5 consecutive years, so the total sample is 280 samples. By using multiple regression analysis, it is found that the existence of foreign commissioner board and intellectual capital has a significant positive effect on firm value. However, the existence of female commissioners, education background, age, and proportion of independent board has no effect on firm value. Keywords : Board diversity, intellectual capital, Tobin's Q, VAIC TM